Students’ Perception of the Presentation Activities in Online Speaking Class - Geminastiti Sakkir; Ahsan Musri S.; Syarifuddin Dollah; Jamaluddin Ahmad (EduLine: Journal of Education and Learning Innovation, 2022)
The objectives of this research were to find out the benefits of presentation activities in online speaking classes. Data were collected using a questionnaire that collected a five-point Likert scale to gauge the students’ perception use of presentation activities in online speaking classes. The population of this research was eleventh-grade students of senior high school 4 Sidrap academic year 2021//2022 through random sampling technique and XI IPA 1 was selected as the sample of this research. The research finding showed that the utilization of presentation activities gave some benefits to the students as follows: easy understanding of the material; increased students’ motivation; focus deeper on learning; and Increased collaboration. It could be concluded that the utilization of presentation activities in online speaking class benefited the students in the eleventh grade of SMAN 4 Sidrap.